The Influence of Islamic Attributes and Destination Image on Intention to Engange in Muslim Friendly Travel: Mediating by Emotional Value and Moderated by Halal Awareness - a Conceptual Paper - Rasyid, Rafika Isya; Dewi, Citra Kusuma; Widodo, Arry; Pradana, Mahir; Hasbi, Imanuddin (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2024)
This research investigates the factors that will influence Muslim tourists' intentions to undertake Muslim-friendly tourism in Bali, amidst the dominant Hindu culture on the island. Specifically, this research examines the impact of Islamic attributes and destination image through tourists' emotional value on intention to engage, with halal awareness moderating this relationship. Methodologically, this quantitative research collected data from 230 Muslim tourists who had visited Bali more than once. Structural Equation Modeling (SEM) and Smart PLS software were used for data analysis. The findings reveal that Islamic attributes and destination image will significantly increase tourists' emotional value, which in turn will positively impact their intention to engage in Muslim-friendly tourism. Halal awareness moderates this relationship, highlighting its role in shaping tourists' perceptions and experiences. These results underscore the importance of developing and promoting Muslim-friendly amenities and services in non-Islamic destinations such as Bali, providing insights for tourism stakeholders to increase the competitiveness and attractiveness of these destinations for Muslim tourists globally.